Tantangan Bakamla sebagai Penjaga Laut Indonesia dalam Meningkatkan Keamanan dan Keselamatan di Perairan Indonesia - Dyah Danastri Anindita Nurdewi (Sosial Simbiosis : Jurnal Integrasi Ilmu Sosial dan Politik, 2024)
This article discusses the challenges faced by Indonesia's Marine Security Agency (Bakamla) in improving security and safety in Indonesian waters, which is the world's largest archipelago. Based on the reality that the importance of Indonesia's vast waters and vulnerability to maritime threats, such as sea crime and smuggling. The purpose of this study is to analyse the challenges of Bakamla and its role as guardian of the sea. The method used is a descriptive qualitative approach, which includes a literature study and in-depth interviews with various relevant parties. The results show that Bakamla faces various constraints, including limited resources, inadequate equipment, and lack of inter-agency coordination. Nonetheless, through a hard power approach and strengthening inter-agency collaboration, Bakamla can strengthen its capacity in maintaining maritime security. This research emphasises the importance of budget support and equipment modernisation to improve Bakamla's effectiveness in protecting Indonesia's maritime interests.